BUCHOLTZ, Mary; CASILLAS, Dolores Inés; SOOK LEE, Jin (org.). Feeling It: Language, Race, and Affect in Latinx Youth Learning: Routledge, 2018. 278 p. ISBN 978.113829.680.0 - Rodrigues, Raquel de Almeida (Cadernos de Linguagem e Sociedade, 2020)
Resenha crítica